Analysis of winning determinant performance indicators according to teams level in Chinese women`s volleyball - Yu, Y.; Garcia-De-Alcaraz, A.; Wang, L.; Liu, T. (International Journal of Performance Analysis in Sport, 2018)
The goal of the study was to identify the performance indicators in relation to set outcome regarding quality of opposition in elite women volleyball. The sample comprised 377 sets played in 100 matches by 12 teams participating in the Chinese Women`s Volleyball Association League (2016-2017). Teams were divided as high, middle and low level according to their ranking at the end of the season. Twelve performance indicators (points and errors in scoring and continuity actions) were chosen and analysed in terms of set outcome (win or lose) and type of confrontation. The results demonstrate that the quality of opposition has a clear influence on team performance. The spike and block, both in points and errors, were the mainly performance indicators related to set outcome. Serve points, serve-reception errors and excellent defences were also significant indicators. This study provides new insights into training and research, and it may be useful to coaches, physical trainers and match analysts for assessing performance and training their teams.